Effect of Patah Tulang Latex (Euphorbia tirucalli L.) on Wound Healing in Wistar Rat - Galuh Ratnawati; Kurniasih - Kurniasih; Surya Amanu (Indonesian Journal of Pharmaceutical Science and Technology, 2019)
Injure healing process occured on four phases such as hemostatis, inflammation, and maturation. Latex of Patah Tulang (Euphorbia tirucalli L.) can heal the wound because of its component active. Aim of this research was to find out the effect of ointment topical of E. tirucalli L. to wound healing process based on macroscopic and microscopic examination and cellular reaction of CD4+ lymphocyte. Male Wistar Rat, 2 month old, 150-200 Gram of body weight, as much as 36 rats. Rats were divided into 4 groups, and were anesthesized before punctioned on the 2 sides of lateral vertebrae. Group one was used as a control, group two was given with the ointment 9% of E. tirucalli L., group three was given with 23% of E. tirucalli L., and group four was given madecassol®. Treatment was given once a day for 15 days. Macroscopical and microscopical changes were observed at the fifth, tenth, and fifteenth day. Macroscopical observation was the diameter of injure. Microscopical observation consisted of epidermal thicness, number of fibroblast, using Haematoxylin and Eosin staining, and cellular reaction of CD4+ lymphocyte using imunohistochemistry. The results showed that topical administration of E. tirucalli ointment 9% and 23% potential to accelerate wistar skin wound healing puncture wounds. There was no difference between E. tirucalli ointment 9% and 23% application to observed parameters.Keywords: Euphorbia tirucalli L., injure healing, macroscopic, microscopic, lymphocyte CD4+